Compatibility and product design in software markets - Bernd Woeckener (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1999)
This paper analyzes the interplay between compatibility and product design decisions in a symmetric software duopoly with network effects. We show that suppliers do not always offer differentiated product designs and compete within the market. Rather, when ever both the significance of the network effects and the costs of compatibility are high, they offer homogeneous and incompatible variants and compete for the market, although this leads to Bertrand competition with zero profits. Moreover, we show that given our symmetric setting, antitrust authorities should never intervene against incompatibility, whereas compatibility arrangements should always be under their scrutiny.
urn:nbn:de:bsz:21-opus-21014
Keywords: 330; Softwareindustrie; Duopol; Produktdifferenzierung; Normung; Network Externalities; Wohlfahrtseffekt; Theorie